The Georgetown Companion to Interreligious Studies - Mosher, Lucinda (Book collections on Project MUSE., 2022)
"The Georgetown Companion to Interreligious Studies is a comprehensive, authoritative, creative, and cutting-edge anthology of fifty essays that, taken as a group, provide insight into (and food for further thought about) sub-categories of a field of academic inquiry that has developed rapidly in recent decades. Interreligious Studies is an academic field in which scholars deliberately draw on at least one other religion in addition to their home tradition when reflecting on worldview questions; an arena in which at least one religious discourse is involved with some other discourse. Hence, Interreligious Studies is inherently multi-disciplinary, bringing together the study of religion(s) with methodologies from the fields of anthropology, sociology, psychology, political science, history, women's studies, ecology, and more. Interreligious Studies gives pride of place to relational, intersectional, and dialogical approaches as it seeks theoretical and practical insights through the examination of how religions relate to each other, to their own internal diversity, to various social systems, to society at large. A recent assessment of Interreligious Studies programs in universities and theological schools indicates that they make wide (but not exclusive) use of comparative and critical methods; that their purposes include cultivation of religious literacy, promotion of dialogue, fostering of citizenship, and professional preparation for leadership in multireligious contexts"--